2023
DOI: 10.1039/d2fo03181g
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive polysaccharides promote gut immunity via different ways

Abstract: Our study revealed that different polysaccharides promote gut immunity in different ways and provided a guideline for the development of superior intestinal immunomodulatory polysaccharides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Increasing evidence has demonstrated that Christensenellaceae_R-7_group and norank_f__Muribaculaceae positively regulate nutrient metabolism, whereas Gastranaerophilales and Clostridia_UCG-014 are related to metabolic diseases. 21 In the current study, association analysis revealed that Bacteroidota and Prevotellaceae_NK3B31_group had positive relationships with beta-D-glucosamine, 1-butylamine, leucine, and glutamic acid in plasma. According to these results, FeSuc supplementation may affect critical metabolites such as beta-D-glucosamine, 1-butylamine, leucine, and glutamic acid via modulating the structure of the microbial composition in sows.…”
Section: Papersupporting
confidence: 48%
“…Increasing evidence has demonstrated that Christensenellaceae_R-7_group and norank_f__Muribaculaceae positively regulate nutrient metabolism, whereas Gastranaerophilales and Clostridia_UCG-014 are related to metabolic diseases. 21 In the current study, association analysis revealed that Bacteroidota and Prevotellaceae_NK3B31_group had positive relationships with beta-D-glucosamine, 1-butylamine, leucine, and glutamic acid in plasma. According to these results, FeSuc supplementation may affect critical metabolites such as beta-D-glucosamine, 1-butylamine, leucine, and glutamic acid via modulating the structure of the microbial composition in sows.…”
Section: Papersupporting
confidence: 48%
“…57 Monoglobus also promotes the production of SCFAs. 58 Compared to the normal group, Lachnospiraceae_UCG-006, Turicibacter, and Bifidobacterium were more abundant in the Zein-TSP treatment group (Fig. 6(C)).…”
Section: Species Difference Analysismentioning
confidence: 87%
“…Monoglobus is a specialized bacterium that breaks down pectin, the main non-cellulosic component of plant cell wall polysaccharides (47,48). Monoglobus promotes the production of short-chain fatty acids and improves the intestinal microenvironment (49). Gut microbes and their metabolites are hubs connecting the liver-brain-reproductive signaling axis to nutritional strategies that regulate laying hen performance, health, and welfare.…”
Section: Discussionmentioning
confidence: 99%